(untitled) (The International Research Journal of Management Science, 2024)
Purpose: This study examines the impact of mergers and acquisitions (M&A) on employee outcomes in Nepalese commercial banks, focusing on key factors such as cultural integration, job stress, job security, and fairness in transfers and promotions. It further explores the role of operating efficiency after M&A in influencing employee performance. Methods/Design: The research utilizes a mixed-methods approach, combining quantitative surveys and qualitative interviews to assess how these factors influence employee work outcomes during M&A transitions. Findings: The results reveal that effective cultural integration, management of job stress, and assurances of job security positively impact employee outcomes. Perceptions of fairness in transfers and promotions are also crucial in maintaining employee satisfaction and performance. Implications/Limitations: This study provides actionable insights for managing M&A transitions, emphasizing the importance of support systems for employee well-being. It addresses a gap in the literature by focusing on the human side of M&A in Nepalese banks, often overshadowed by financial aspects. However, the small sample size and potential employee response bias may limit the generalizability of the findings. The focus on commercial banks may also restrict the applicability to other sectors. Future research should include more industries and larger samples to better understand long-term employee outcomes post-M&A.